New paradigm of human resources development : government initiatives for economic growth and social integration in Korea - Kim, Jang-Ho [Herausgeber] (Korea Research Institute for Vocational Education and Training, 2005)
"In the knowledge-based society of the 21st century, the prosperity of nations increasingly depends on knowledge and innovative capabilities. More specifically, labor productivity, companies' innovative capabilities and government's efficiency are growing in importance. To enhance these factors, it is utmost important to expand and deepen knowledge, which is a key factor in competitivenes in a knowledge-based society. Unlike physical capital, knowledge needs to be accumalted in people for it to be manifested as productivity and innovative capabilities. Hence, human resources development which raises the knowledge of all members of the society is the essence of national growth strategy. This book has been published in recognition that human resources development is the driving force for new growth paradigm in the knowledge-based society, and it examines human resources development in Korea and seeks to find new national growth strategies. The publication looks at why human resources development is so crucial for the Korean economy, where it currently stands, and what kind of strategies needs to be implemented in order for Korea to achive sustainable growth." (Publisher, BIBB-Doku)
Keywords: G 1.1 Soziostrukturelle & Ökonomische Entwicklungen; S System beruflicher Bildung; S 4.3.6 Human Capital; L 5 Beratung & Orientierung; L 4.2.3 Internetbasiertes Lernen / E-Learning; I 2.3.4 Asien; Personalmanagement; Bildungspolitik; Wirtschaftswachstum; Berufsbildungssystem; Berufliche Weiterbildung; Berufsberatung; Laufbahnberatung; E-Learning; Südkorea